Research of the ECAL calorimeter used in the COMET experiment - Kalinnikov, V.; Velicheva, E. (Functional Materials, 2015)
Based on the real optical model received with the Geant4 simulation, the optimal structure and geometry of the COMET calorimeter was developed, the influence of the shower was studied and energy deposition and calorimeter energy resolution (equal to 4.8 % for the LYSO crystal calorimeter and 6.0 % for the GSO crystal calorimeter) was defined. There was suggested and experimentally tested the algorithm of spatial reconstruction of events in the calorimeter allowing to improve the determination accuracy of the energy deposition value in 2.8 times.